Design and Synthesis of Single-Actuator Walking Robots via Coupling of Linkages - Zhang, Yang; Arakelian, Vigen (Frontiers in Mechanical Engineering, 2021)
This paper deals with the development of single actuator walking robots designed by coupling of two mechanisms. The advantages of such robots are the simplicity of the design and its control system. In this paper, three various design concepts are carried out via coupling of two units which are four-bar linkages, slider-crank mechanisms, and a cam mechanism and a pantograph linkage. The geometrical syntheses of these mechanisms have been analyzed, and based on them, analytical and numerical methods have been adopted to ensure the reproduction of given trajectory similar to the human walking gait. Three single-actuator robots have been designer based on these mechanisms where two of them can be easily reconfigured to reproduce gaits with different lengths or even tilted gaits which can let the robot be able to climb up stairs. All suggested design concepts have been validated through CAD simulations carried out via ADAMS software.